Perancangan Aplikasi RaKJa Untuk Kinerja Ruas Jalan Berbasis Android - Twidi Bethary, Rindu; Krisdianto, Nanang; Fikri Ramadhan, Nurul (Jurnal Teknik Sipil, 2024)
Abstract Performance analysis of road sections is usually carried out on road sections that have the potential for high traffic jams, then perform performance calculations and obtain recommendations for problems on these road sections. However, currently it is still difficult to calculate road performance because it has to be done manually in the calculations and looking for the necessary factors. This research aims to create an application to assist in calculating the performance of Android-based roads more easily and flexibly, this application is called RAKJa (Road Performance Analysis Design) which will be published generally on the Google Play Store so that it can be used by anyone who needs it. This RAKJa application will be developed based on the Indonesian Road Capacity Guidelines (PKJI 2014), this application gets results in the form of degree of saturation, level of service, average speed, delays and queue length automatically without needing to look for the required factors in the PKJI 2014 table. Application This RAKJa was created using the Game Maker Language programming language from the Game Maker Studio 2 developer. Calculation of road performance using the RAKJa application produces the same results as calculations carried out manually. Validating the accuracy of the application from previous research urban road performance data based on the PKJI 2014 and primary data obtained accurate results of 90%.